Knowledge transfer and translation in cultural ecosystems. Issue 9 (5th November 2020) - Dameri, Renata Paola; Demartini, Paola
Abstract : Purpose: This paper concerns the pivotal role that entrepreneurial universities can play in developing knowledge transfer and translation processes tailored to the cultural ecosystem. Design/methodology/approach: The paper examines IncubiAmo Cultura, an innovative project that aims to mentor potential entrepreneurs and offer incubation and acceleration for cultural start-ups. The research methodology is based on action research and theory building from cases. An interventionist approach has been adopted, as one of the authors is also the founder of the ongoing project. Findings: The in-depth collection of first-hand information on this pilot project has allowed the authors to formulate an analytical reflection and generate the design of a knowledge translation model driven by an entrepreneurial university that manifests itself through the creation of cultural and creative start-ups. Research limitations/implications: This article offers an original contribution to scholarship by offering a conceptual model for knowledge translation in cultural ecosystems. Common values (i.e. social, cultural, ethical and aesthetic ones) emerge as the basis on which to build open innovation and knowledge circulation. Practical implications: For local policymakers, this study provides a clue to understand the need for both an integrated vision of knowledge translation and policies that aim to make an impact at the cultural ecosystem level. For entrepreneurial university governance, our investigation offers suggestions on the design and implementation of knowledge translation processes that fit with the specificity of the cultural ecosystem. For practitioners in the cultural field, a change of mindset is required to combine resources, energies and knowledge. Originality/value: This work fills several gaps in the literature, as research generally concerns knowledge transfer from entrepreneurial universities to the market with regard to high-tech sectors. In contrast, the cultural sector is often neglected, despite its importance in the renewal and development of a territory.